CHARACTERIZATION OF A SMALL FOV PORTABLE GC: MediPROBE. Issue 1 (11th December 2018) - Acampa, Wanda; Capussela, Tiziana; Cuocolo, Alberto; Di Lillo, Francesca; Punzo, Giorgio; Quarto, Maria; Roberti, Giuseppe; Russo, Paolo; Serra, Marcello
Abstaract: In this work, we evaluated the performance of the prototype SFOV MediPROBE developed at the University of Naples Federico II through the protocol proposed by (Bhatia B.S., Bugby S.L., Lees J.E., Perkins A.C. A scheme for assessing the performance characteristics of a small field of-view gamma cameras. Physica. Medica., 31 (1), pp. 98–103. (2015) doi: 10.1016/j.ejmp.2014.08.004). We extensively investigated a new device configuration where the pinhole collimator was placed outside the housing of the probe, in order to increase the system spatial resolution, and the pixel size was doubled, in order to reduce the charge sharing effect. The experimental measurements show that the spatial resolution is enhanced by only about 10%, but the sensitivity decreases strongly. Therefore, the trade-off between these two features does not seem to be advantageous. In addition, our experiments suggest that the charge sharing effect is not completely canceled. Despite these results, the features of this device appear suitable for intraoperative surgical survey. We aim to use this device in the clinical practice for the intraoperative imaging of lymph nodes, breast, thyroid and parathyroid tumors.